(untitled) (Papeles, 2010)
According to the author’s perspective, the study of fighting dogs is a reflection work carried out during three months of inquiries and consultations about the fighting dogs in Bogotá Colombia. This article shows the following results: 1- Description the dog’s fighting groups like one “Speaking community” 2- To Know features of “fighting dogs” 3- To establish the fighting dogs as a “Speaking events” In Bogotá City there groups of people dedicated in this activity carries out in three major areas: North, Centre and South of the town, so that for this work was a follow-up among a groups of dog’s fighting in Kennedy locality. First of all, the researched spoke with this community of fighting dogs in informal way, then she performed three semi-open interviews; finally it is important to clarify that the information presented in this article don’t reflects an acceptance of this activity by the author. It only constitutes an ethnographic approach to knowledge of “dog’s fighting”